Cryptocurrency from Shariah perspective - Oziev, Gapur; Yandiev, Magomet (IIUM Press, International Islamic University Malaysia, 2018)
For the past few years there has been a significant increase of people’s interest in crypto-currencies. Seminars and conferences have been organized to discuss the nature and feasibility of cryptocurrencies. Some argue that it is good to have an alternative to the current fiat money system in which the predominant role is played by banks, while a cryptocurrency does not require any bank account, tax payment and auditing. Some others disagree with these arguments and claim that any mode of payment in other than traditionally known instruments such as cash payment, telegraphic-transfers, cheques and so, will open the door to avoid tax and audits, which in turn may seriously effect a government’s budget and may even decrease GDP. This research uses theoretical, descriptive and analytical methods of research and therefore focuses on the following important points: a) defining the place of cryptocurrency in the financial system by determining the extent of its influence; b) reviewing the literature on the topic, which will allow us to determine the current understanding of the problem by modern science; c) unveiling the key requirements of Shari’ah for money and money circulation to formulate a standard understanding of money in Shari’ah; d) comparing the characteristics of paper money and crypto-currencies (using the bitcoins as an example). The authors believe in permissibility of using the cryptocurrencies but with strict reservations.